The Electrophoretic Deposition of Nano Al2O3 and AgNO3 on CpTi Dental Implant (An in vitro and in vivo study) - Rsul N Turky; Raghdaa K Jassim (College of Dentistry/ University of Baghdad, 2016)
Background: Even the wide use of dental implants, still there is a proportion of implants are failed due to infection. Much considerable attention has been paid to modify the implant surface. Coating of dental implant with a biocomposite material of suitable properties can improve osseointegration. And this is the main concern of this study. The aim of present study was to evaluate the use of a biocomposite coating of dental implant with (ceramic nano Al2O3 and metalic AgNo3) on the bond strength at bone - implant interface and tissue reaction. Materials and methods: A total number of forty-eight screws, CpTi dental implant used in this study. Half of these screws were coated with a biocomposite material of nano (Al2O3and AgNo3), this was done by using electrophoretic deposition method (EFD). In invitro part of the study, analysis of the coated surface was done using: X ray diffraction (XRD), atomic force microscope (AFM), Energy Dispersive X-ray spectroscopy (EDX), Optical microscopy and Scanning electron microscope (SEM). In invivo part of study, 10 white male New Zealand rabbits were used, and a screw type of dental implant [uncoated and coated with nano (Al2O3and AgNo3)] were implanted in each tibia of rabbit. Then biomechanical and Histological test were performed after 2 and 4 weeks healing intervals. Results: The results of biomechanical test showed a higher torque mean values of (M+SD):(14.91N.cm+2.7)and (22.5 N.cm +5.31) after 2 and 4 weeks respectively. In histological examination of coated screws at 2 weeks, there isa bone trabeculae occupies a base of implant bed with osteoblast andosteocyte. At 4 weeks, there is a progress in the healing process around dental implant, and this includes: -new bone with haversian canals, osteoblast and osteocyte. Conclusion: Biocomposite coating of dental implant with Alumina and silver nitrate can be made by electrophoretic deposition method (EPD), and a multifunctional surface has been created. Keywords: Electrophoretic Deposition, alumina, screw Dental Implants, torque.